La plus ancienne version en langue romane de la légende apocryphe néronienne : Si comme Nero, uns empereres, fist decoler saint Piere et saint Pol et fist ovrir se mere (Carte Romanze, 2022)
The famous miscellaneous manuscript Bnf, fr. 1553 (1284-1285) hands down several unica of great interest: one of these is the Old French translation (Picard variety) of the text titled Si comme Nero, uns empereres, fist decoler saint Piere et saint Pol et fist overe se mere, which has remained unpublished until now and dates to around the middle of the 13th century. A critical edition with philological and linguistic commentary is proposed.